It's all in the combination: decoding the epigenome for cancer research and diagnostics. (April 2022) - Furth, Noa; Shema, Efrat
Abstract : Genome regulation is governed by the dynamics of chromatin modifications. The extensive and diverse array of DNA and histone modifications allow multiple elements to act combinatorically and direct tissue-specific and cell-specific outcomes. Yet, our ability to elucidate these complex combinations and link them to normal genome regulation, as well as understand their deregulation in cancer, has been hindered by the lack of suitable technologies. Here, we describe recent findings indicating the importance of the combinatorial epigenome, and novel methodologies to measure and characterize these combinations. These complementary methods span multiple disciplines, providing a means to decode epigenetic combinations and link them to biological outcomes. Finally, we discuss the promise of harnessing the rich combinatorial epigenetic information to improve cancer diagnostics and monitoring.